Integrating gender in ergonomic analysis: strategies for transforming women's work (Brussels, 1999)
"For a number of years past, the Montreal-based CINBIOSE centre (the Centre for the study of biological interactions in environmental health - University of Quebec) has been conducting research to make visible and gain recognition for aspects of women's work which are bad for their physical or mental health. This research stems from the concerns and needs voiced by women workers themselves. Most of it is conducted in partnership with the three main Quebec trade unions. Through their scientific research and commitment to making workplaces healthy and safe, the team aims to shed light on what has so far remained invisible. We thought this was a lead which should be brought to European attention. It shows the immense potential contribution of action-oriented research to improving equal opportunities and working conditions."